The wizard of Oz : the graphic novel - Cavallaro, Michael, 1969- (Puffin graphics, 2005)
A graphic novel adaptation of L. Frank Baum's story in which a young girl named Dorothy is transported by a cyclone to the land of Oz and befriended by a scarecrow, a tin man, and a cowardly lion, who accompany her to the Emerald City to look for a wizard who can help her return home.